2005
DOI: 10.1007/s00066-005-1353-3
|View full text |Cite
|
Sign up to set email alerts
|

Amifostine is a Potent Radioprotector of Salivary Glands in Radioiodine Therapy

Abstract: The results indicate that parenchymal damage in salivary glands induced by high-dose radioiodine therapy can significantly be reduced by amifostine. Therefore, amifostine therapy may increase quality of life in patients with differentiated thyroid cancer after radioiodine treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 54 publications
1
21
0
Order By: Relevance
“…Apoptosis is considered a possible mechanism of SG damage induced by RAI (20). In the present study, TUNEL assays revealed more apoptotic cells in both acini and ducts in RAI-treated mice, indicating that ductal and acinar cells were damaged by RAI.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…Apoptosis is considered a possible mechanism of SG damage induced by RAI (20). In the present study, TUNEL assays revealed more apoptotic cells in both acini and ducts in RAI-treated mice, indicating that ductal and acinar cells were damaged by RAI.…”
Section: Discussionsupporting
confidence: 57%
“…RAI-treated SGs revealed nonspecific manifestations of cellular injury combined with acinar loss and disorganization, and in some animals, glandular duct enlargement and marked lipomatosis were observed (4,(20)(21)(22). Furthermore, SGs in RAI-treated mice showed pale cytoplasm, atypical ductal configuration, septal widening, lymphocyte infiltration, cytoplasmic vacuolization with pleomorphism, and increasing fibrosis in tissues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most convincing results are available for a reduction of radiation-induced xerostomia [5,25]. A recent meta-analysis [29] revealed positive effects also for other organs, but nonblinded studies were included.…”
Section: Introductionmentioning
confidence: 99%
“…Preclinical studies reported that while amifostine (Ethyol ® ) decreased the level of damage to the parotid gland due to its cytoprotective property, it also protected normal tissues other than the parotid gland against the side effects of RT and chemotherapy (CT). [11][12][13][14][15][16][17][18] Amifostine is a phosphorylated aminothiol (WR2721) prodrug that preferentially accumulates in the salivary gland where it is metabolized to its active form by alkaline phosphatase, WR1065. 19 This active metabolite acts as a free radical scavenger and is considered the effective cytoprotector against side effects of both CT and RT.…”
mentioning
confidence: 99%